A Marvel of Virtue: Castelvetro on Laura’s Chasteness in the Rerum vulgarium fragmenta - Mussio, Thomas E. (Quaderni d'Italianistica, 2025)
This article holds that compared to other fifteenth- and sixteenth-century commentaries on Petrarch’s Rerum vulgarium fragmenta Castelvetro’s commentary is unusual in its insistence on a non-sexual but constantly loving Laura whose chaste virtue saves the speaker from desperation and vice. Castelvetro’s view of Laura as a marvel of virtue does not merely reflect the reformist bent of Castelvetro’s Protestant thought but also expresses his reconstruction of the love narrative of the Rvf, which features Laura is an active agent whose attitude towards the speaker may vacillate, but whose love for him and chaste virtue remain, importantly, constant.